2016
DOI: 10.17140/droj-2-126
|View full text |Cite
|
Sign up to set email alerts
|

Unexplained Hypoglycaemia and Large Glycaemic Variability: Skin Lipohypertrophy as a Predictive Sign

Abstract: Strollo F, Guarino G, Armentano V, et al on behalf of AMD-OSDI Italian Study Group on Injection Techniques. Unexplained hypoglycaemia and large glycaemic variability: Skin lipohypertrophy as a predictive sign.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…Consequently, in past publications we have also criticized research groups unable to adopt a strict, repeatable, and safe LH identification method [8,10,11]. Even more, we have pronounced the high prevalence of LH lesions as evidence that clinicians are not sufficiently interested in this problem and have allowed patients to carry out their insulin treatment in a non-systematic and somewhat careless manner [30,31]. Such criticism sounds like a defeat for clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, in past publications we have also criticized research groups unable to adopt a strict, repeatable, and safe LH identification method [8,10,11]. Even more, we have pronounced the high prevalence of LH lesions as evidence that clinicians are not sufficiently interested in this problem and have allowed patients to carry out their insulin treatment in a non-systematic and somewhat careless manner [30,31]. Such criticism sounds like a defeat for clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Patil et al found that “twenty-five (11.1%) subjects had noticed persistent swelling at their injection sites suggestive of the LH”, which in fact might not reflect actual LH presence [33]. Conversely, in a series of 387 people with T2DM [10], LH prevalence was as high as 77% according to a structured LH investigation method utilized by well-trained health professionals already successfully involved in LH-related studies [30, 31]. In addition to that, as pointed out by some authors, LH prevalence among studies may vary depending on lack of routine skin examination in diabetes clinics and/or on missed adherence to validated methods by poorly experienced health professionals [34, 35].…”
Section: Discussionmentioning
confidence: 99%
“…Another factor eventually contributing to HYPO and GV rate and adding to comorbidities typically found in dialyzed patients might be the presence of insulin-related skin lipohypertrophy (LH) [1015]. Indeed LH has been shown to deteriorate both quality of life [11] and glycemic control [16, 17] despite increased insulin dosage [11], thus raising costs [30] as a result of higher acute/chronic complications and emergency room access rates [12, 18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it should be emphasized that suboptimal glycemic control and in patients with unexplained hypoglycemia, treating physicians should inspect and examine the presence of LH. 21 Repeated trauma to the same injection site when patients fail to rotate injections and/or repeated use of the same needle was reported worldwide. 5 The patient usually finds less painful injection when injected into LH area, and this could further aggravate the enlargement of LH area.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it should be emphasized that suboptimal glycemic control and in patients with unexplained hypoglycemia, treating physicians should inspect and examine the presence of LH. 21 …”
Section: Discussionmentioning
confidence: 99%